Does Partisanship Shape Investor Beliefs? Evidence from the COVID-19 Pandemic. (29th September 2020) - Cookson, J Anthony; Engelberg, Joseph E; Mullins, William
Abstract: We use party-identifying language—like "liberal media" and "MAGA"—to identify Republican users on the investor social platform StockTwits. Using a difference-in-difference design, we find that partisan Republicans remain relatively unfazed in their beliefs about equities during the COVID-19 pandemic, while other users become considerably more pessimistic. In cross-sectional tests, we find Republicans become relatively more optimistic about stocks that suffered the most during the COVID-19 crisis, but more pessimistic about Chinese stocks. Finally, stocks with the greatest partisan disagreement on StockTwits have significantly more trading in the broader market, explaining 28% of the increase in stock turnover during the pandemic. Authors have furnished data and an Internet Appendix, which are available on the Oxford University Press Web site next to the link to the final published paper online.